A bibliometric and visual analysis of obesity and polycystic ovary syndrome from 2012 to 2022 - Luo, Ping; Li, Jiake; Li, Pengzhou; Wang, Guohui; Li, Weizheng; Song, Zhi; Sun, Xulong; Fu, Zhibing; Zhou, Hui; Yi, Xianhao; Zhu, Liyong; Zhu, Shaihong (Frontiers in Endocrinology, 2022)
Abstract Background Obesity is associated with polycystic ovary syndrome (PCOS). We aimed to elucidate the research status and explore research trends and future directions. Methods Based on the database of Web of Science Core Collection, bibliometric analyses were conducted with the published papers in the field of obesity and PCOS from 2012 to 2022. VOSviewer software was used to statistically analyze and visualize the collaboration networks, research trends, literature sources, citation and co-citation analysis, and keywords analysis. Results We retrieved 2843 records, which were published in 681 journals by 12307 authors from 2942 institutes in 99 countries. The number of published papers and citations had a roughly increasing trend annually. The United States and China contributed to most of the records included. Monash University, Shanghai Jiaotong University, Aristotle University of Thessaloniki, Karolinska Institution, University of São Paulo, and Tehran University of Medical Sciences were the biggest nodes in their cluster of the collaboration network map, and Moran LJ, Teede HJ, Joham AE, Escobar-Morreale HF, and Macut D were prolific authors. Research trends and hotspots were identified and visualized in the field of obesity and PCOS. Conclusions We concluded the research status and trends in the field of obesity and PCOS. It may be helpful for researchers to understand the collaboration patterns, research hotspots, and frontiers.